From the Garden City to the Smart City - Hügel, Stephan (2017)
It has been a century since the first Garden Cities at Welwyn and Letchworth were founded and, in the eyes of many, we have entered the age of the Smart City. This commentary briefly reflects upon the origins of Ebenezer Howard’s vision in the slums of overcrowded, filthy London and the fire-traps of early 20th century Chicago before outlining some of the main contributing factors to its ultimate failure as an approach: the lack of a robust theory underpinning his ideas, a finance model which was unacceptable to the banks—leading to a compromise which robbed the more idealistic participants of any real power over their schemes—and finally, a dilution of Howard’s vision by architects who were more focused on population density than on social reform. A parallel is then drawn between the weaknesses which afflicted the Garden City vision, and those which afflict current Smart City visions, a loose agglomeration of ahistorical techno-utopian imaginaries, whose aims almost invariably include optimising various measures of efficiency using large-scale deployments of networked sensors and cameras, linked to monolithic control rooms from which our shared urban existence is overseen. The evolution (or perhaps more accurately: alteration) of these concepts in response to criticism is then detailed, before some of the less well-known ideas which are now emerging are briefly discussed.